Implementasi Metode Talaqqi Terhadap Kemahiran Membaca Al-Qur’an Santri Rumah Qur’an Desa Tajurhalang Kabupaten Bogor - Nur Sholihatun Nisya; Indry Nirma Yunizul Pesha; Sofian Muhlisin (At-Tadris: Journal of Islamic Education, 2026)
The ability to read the Quran correctly is an essential skill for every Muslim. At the Tajurhalang Village Quran House, the Talaqqi method is used as the primary approach in Quran learning, where teachers directly guide students to ensure recitation follows the rules of Tajweed. This study aims to determine the implementation of the Talaqqi method on Quran reading skills at the Tajurhalang Village Quran House. The research employed a qualitative descriptive approach. Data collection was conducted through interviews and observations of students and teachers at the Quran House. This study focused on the process of implementing the Talaqqi method and its impact on improving Quran reading skills. The results indicate that the Talaqqi method has a positive impact on Quran reading skills. This is evident in the students' improved ability to read the Quran more fluently, accurately, and in accordance with the rules of Tajweed. Based on interviews with 20 students, the data obtained by the researchers showed that 14 students stated that the implementation of the Talaqqi method was very effective and had a positive impact on their Quran reading skills. The other six students stated that they still needed improvement and specific guidance from their teachers. The success of this method is supported by adequate facilities, learning resources, teacher support, and motivation and support from parents. A barrier to the Talaqqi method is the students' limited study time, which prevents them from achieving optimal results.